IMPLEMENTASI KEBIJAKAN PERENCANAAN DAN PENGANGGARAN YANG RESPONSIF GENDER DI PEMERINTAH KOTA PALEMBANG - Antasari, Rr. Rina; Hadi, Abdul (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
In every current National Government policy, it explicitly makes women and children an integral part of the overall achievement of full human rights fulfillment in Indonesia. This is stated in the second priority agenda of Nawacita namely: increasing the role and representation of women in politics and development. Others are stated also in the eighth priority agenda of Nawacita: protecting children, women and marginalized groups. In this context, the strategic issues to be addressed during the 2015-2019 development period are: (1) improving the quality of life and the role of women in various fields of development; (2) protection of women against various acts of violence including TPPPO; and (3) enhancement of institutional capacity of PUG and institutional protection of women from various acts of violence. This article will examine the implementation of gender responsive planning and budgeting policies with case studies in the city government of Palembang.